Challenges in drug target discovery in bipolar disorder. (June 2013) - Alsaif, Murtada; Haenisch, Frieder; Guest, Paul C; Rahmoune, Hassan; Bahn, Sabine
<x xml:space="preserve">Abstract</x> Introduction: Misdiagnosis and subsequent inappropriate treatment of patients with bipolar disorder (BD) can worsen their clinical condition and outcome. Areas covered: This review focuses on the therapeutic targets which have been implicated in BD, including the glycogen synthase kinase 3 (GSK-3) and phosphoinositide signaling pathways. In addition, evidence is presented for potential new molecular strategies which involve targeting neuropeptide-converting endopeptidases, glutamatergic excitotoxicity, insulin signaling and dysfunctions in mitochondrial metabolism. Current limitations in study design, molecular platforms, preclinical and cellular models in the context of BD drug target discovery, suggest that there are many areas for improvement. Expert opinion: For the future outlook, this review outlines the importance of developments such as the use of BD patient-derived cellular models for providing better understanding of the BD etiology and robust translational drug screening tools in combination with developments in the fields of bioinformatics and systems biology.